Increased Hypothalamic Projections to the Lateral Hypothalamus and Responses to Leptin in Rat Neonates From High Fat Fed Mothers - Kelley, Lyla; Verlezza, Silvanna; Long, Hong; Loka, Mary; Walker, Claire-Dominique (Frontiers in Neuroscience, 2020)
The lateral hypothalamus (LHA) is a central hub in the regulation of food intake and metabolism, as it integrates homeostatic and hedonic circuits. During early development, maturing input to and output from the LHA might be particularly sensitive to environmental dietary changes. We examined the effects of a maternal high fat diet (HFD, 60% Kcal in fat) on the density of hypothalamic projections to the orexin (ORX-A) field of the LHA in 10 day-old (PND10) rat pups using retrograde labeling with fluorescent microspheres. We also compared responsiveness of phenotypically identified LHA neurons to leptin administration (3 mg/kg, bw) between pups from control (CD) or high fat (HFD) fed mothers on PND10 and 15-16, at the onset of independent feeding. HFD pups exhibited a higher density of LHA projections (p = 0.05) from the ventromedial hypothalamus (VMH) compared to CD pups and these originated from both SF-1 and BDNF-positive neurons in the VMH. Increased circulating leptin levels in HFD pups, particularly on PND15-16 was consistent with enhanced pSTAT3 responses to leptin in the orexin (ORX-A) field of the LHA, with some of the activated neurons expressing a GABA, but not CART phenotype. ORX-A neurons colocalizing with pERK were significantly higher in PND15-16 HFD pups compared to CD pups, and leptin-induced increase in pERK signaling was only observed in CD pups. There was no significant effect of leptin on pERK in HFD pups. These results suggest that perinatal maternal high fat feeding increases hypothalamic projections to the ORX-A field of the LHA, increases basal activation of ORX-A neurons and direct responsiveness of LHA neurons to leptin. Since these various LHA neuronal populations project quite heavily to Dopamine (DA) neurons in the ventral tegmental area, they might participate in the early dietary programming of mesocorticolimbic reward circuits and food intake.